Character association and path coefficient analysis for identification of yield enhancing characters in snake gourd (Trichosanthes anguina L.) (Jahangirnagar University Journal of Biological Sciences, 2016)
Correlations and path coefficient were studied in seven snake gourd genotypes namely Turag, Surma, Vorosa, Manghosito, Jhumlong, Green nitch and Monosha for yield and eleven yield contributing characters. The correlation coefficients were determined to find out the interrelationship among the characters studied. The correlation studies revealed that, yield/plant had positive and highly significant correlation both in phenotypic and genotypic level with fresh weight/fruit, fruit girth, fruits/plant, plant height and fruit length which indicated that yield could be increased by selecting these characters. Direct and indirect effects were measured using path coefficient analysis in order to obtain mechanisms of interrelationship between yield/plant and its components. The highest positive direct effect (0.9763) on yield/plant was found in fresh weight/fruit followed by fruits/plant (0.4179) and fruit length (0.2665). The characters showed direct positive effect on yield/plant indicated that direct selection for these traits might be effective for improving yield through selection in snake gourd.Jahangirnagar University J. Biol. Sci. 3(2): 57-65, 2014 (December)